2018
DOI: 10.1002/cam4.1519
|View full text |Cite
|
Sign up to set email alerts
|

Contralateral prophylactic mastectomy rate and predictive factors among patients with breast cancer who underwent multigene panel testing for hereditary cancer

Abstract: Although multigene panel testing is increasingly common in patients with cancer, the relationship between its use among breast cancer patients with non‐BRCA mutations or variants of uncertain significance (VUS) and disease management decisions has not been well described. This study evaluated the rate and predictive factors of CPM patients who underwent multigene panel testing. Three hundred and fourteen patients with breast cancer who underwent multigene panel testing between 2014 and 2017 were included in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 41 publications
3
21
3
Order By: Relevance
“…As recently reported, having BRCA-positive breast cancer may also influence carboplatin or PARP-inhibitor drug selection. [12][13][14][15][16] A second major point of consensus, discussed in more detail in the following, is that clinical data overall fairly consistently demonstrate no increased risk of radiation toxicity or radiation-induced second cancers in germline BRCA1 or BRCA2 mutation carriers treated with standard adjuvant radiation regimens. [17][18][19][20] The absence of a radiation therapyerelated detriment among BRCA carriers may provide some reassurance regarding phenotypically similar heterozygous germline DNA repair variants, such as pathogenic PALB2 and CHEK2 alleles.…”
Section: Current Germline and Somatic Tumor Genomic Screening In Clinmentioning
confidence: 98%
“…As recently reported, having BRCA-positive breast cancer may also influence carboplatin or PARP-inhibitor drug selection. [12][13][14][15][16] A second major point of consensus, discussed in more detail in the following, is that clinical data overall fairly consistently demonstrate no increased risk of radiation toxicity or radiation-induced second cancers in germline BRCA1 or BRCA2 mutation carriers treated with standard adjuvant radiation regimens. [17][18][19][20] The absence of a radiation therapyerelated detriment among BRCA carriers may provide some reassurance regarding phenotypically similar heterozygous germline DNA repair variants, such as pathogenic PALB2 and CHEK2 alleles.…”
Section: Current Germline and Somatic Tumor Genomic Screening In Clinmentioning
confidence: 98%
“…As the genetic testing was restricted to BRCA1 and BRCA2, other studies will be needed to assess the impact of positive test results for moderate risk genes, such as PALB2, CHEK2, and ATM. Interestingly, a CPM uptake comparable to BRCA carriers was recently reported for non-BRCA carriers with positive multigene panel testing results [24].…”
Section: Discussionmentioning
confidence: 67%
“…There are a number of studies that have assessed the impact of genetic testing on CRRM rates [34][35][36] . A recent study from Denmark 35 confirmed that uptake of CRRM amongst women before the age of 45 years was significantly higher in those harbouring a pathogenic variant of the BRCA1/2 gene and those from high-risk families, compared to those with a lower genetic risk.…”
Section: Discussionmentioning
confidence: 99%